Altitudinal variation in butterfly community associated with climate and vegetation - PIRES, ANA CAROLINA V.; BARBOSA, MILTON; BEIROZ, WALLACE; BEIRÃO, MARINA V.; MARINI-FILHO, ONILDO J.; DUARTE, MARCELO; MIELKE, OLAF H.H.; LADEIRA, FABIOLA A.; NUNES, YULE R.F.; NEGREIROS, DANIEL; FERNANDES, GERALDO W. (Anais da Academia Brasileira de Ciências, 2020)
Elevation creates a variety of physical conditions in a relatively short distance, which makes mountains suitable for studying the effects of climate change on biodiversity. We investigated the importance of climate and vegetation for the distribution of butterflies from 800 to 1400 m elevation. We sampled butterflies, and woody and rosette plants and measured air temperature and humidity, wind speed and gust, and solar radiation. We partitioned diversity to assess the processes underlying community shifts across altitudes - species loss versus replacement. We assessed the strength of the association among butterfly, vegetation, and climate. Butterfly richness and abundance decreased with altitude, and species composition changed along the elevation. Changes in butterfly composition with altitude were mainly through species replacement and by abundance increases in some species being compensated by decreases in others. Since the floristic diversity decreased with altitude due to soil conditions, and butterflies are closely related to their host plants, this could explain species replacement with altitude. Overall, we found a stronger association of butterfly community with vegetation than climate, but plant community and climate were also strongly associated between them. Butterfly richness was more strongly associated with plant richness than with temperature, while the reverse was true for butterfly abundance, which was more strongly associated with temperature than with plant richness. We must consider the complementary roles of resource and conditions in species distribution.Elevation creates a variety of physical conditions in a relatively short distance, which makes mountains suitable for studying the effects of climate change on biodiversity. We investigated the importance of climate and vegetation for the distribution of butterflies from 800 to 1400 m elevation. We sampled butterflies, and woody and rosette plants and measured air temperature and humidity, wind speed and gust, and solar radiation. We partitioned diversity to assess the processes underlying community shifts across altitudes - species loss versus replacement. We assessed the strength of the association among butterfly, vegetation, and climate. Butterfly richness and abundance decreased with altitude, and species composition changed along the elevation. Changes in butterfly composition with altitude were mainly through species replacement and by abundance increases in some species being compensated by decreases in others. Since the floristic diversity decreased with altitude due to soil conditions, and butterflies are closely related to their host plants, this could explain species replacement with altitude. Overall, we found a stronger association of butterfly community with vegetation than climate, but plant community and climate were also strongly associated between them. Butterfly richness was more strongly associated with plant richness than with temperature, while the reverse was true for butterfly abundance, which was more strongly associated with temperature than with plant richness. We must consider the complementary roles of resource and conditions in species distribution.